2004
DOI: 10.1111/j.1475-4754.2004.00172.x
|View full text |Cite
|
Sign up to set email alerts
|

Archaeometric Study of Protohistoric Grinding Tools of Volcanic Rocks Found in the Karst (Italy–slovenia) and Istria (Croatia)*

Abstract: This paper presents the results of the archaeometric study of 30 grinding tools found in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 23 publications
(41 reference statements)
2
31
0
Order By: Relevance
“…Maritan et al. () already outlined a discrepancy between the concentrations of some elements (e.g., Ti, Th, Sr, and Zr) reported in the reference database and those published later, determined on bulk‐rock samples by either XRF or solution ICP‐MS, even by the same authors of the database (Antonelli & Lazzarini, ; Antonelli et al., ; Capedri & Venturelli, ; ; Capedri et al., ; Renzulli, Santi, Serri, & Luni, ). This is further confirmed here and illustrated in Figure in the Sr/Th plot, the main discriminant diagram by Capedri et al.…”
Section: Geochemical Tracersmentioning
confidence: 95%
See 1 more Smart Citation
“…Maritan et al. () already outlined a discrepancy between the concentrations of some elements (e.g., Ti, Th, Sr, and Zr) reported in the reference database and those published later, determined on bulk‐rock samples by either XRF or solution ICP‐MS, even by the same authors of the database (Antonelli & Lazzarini, ; Antonelli et al., ; Capedri & Venturelli, ; ; Capedri et al., ; Renzulli, Santi, Serri, & Luni, ). This is further confirmed here and illustrated in Figure in the Sr/Th plot, the main discriminant diagram by Capedri et al.…”
Section: Geochemical Tracersmentioning
confidence: 95%
“…The first evidence of Euganean trachyte exploitation dates back to prehistoric times (Neolithic, 5th millennium BCE) (Bianchin Citton & De Vecchi, 2009), although a greater number of records have been reported from protohistory and the pre-Roman period, within the territories controlled by the Venetic civilization as well as the Etruscans. The crafting of querns was well established, but trachyte was also used in build-ing construction, necropolises, for funerary and votive cippi and stelae (Bianchin Citton & De Vecchi, 2009;Cattani, Lazzarini, & Falcone, 1997, Antonelli, Bernardini, Capedri, Lazzarini, & Montagnari Kokelj, 2004, and even as temper in pottery production (Calogero & Lazzarini, 1984;Maritan, 2004;Maritan, Mazzoli, Rigaldo, Pesavento Mattioli, & Mazzocchin, 2006). Later, Roman domination led to widespread usage of Euganean trachyte (Lazzaro, 1992;Zara, 2016), which was frequently transported by ship along the numerous waterways of the Venetian Plain, the Po River, and in the Adriatic Sea (Germinario et al, 2018;Renzulli, Antonelli, Santi, Busdraghi, & Luni, 1999;2002b).…”
Section: Historical Outlinementioning
confidence: 99%
“…Capedri et al, 2000). Gray filled circles refer to three Roman mills from Antonelli et al, 2004 and one Roman millstone from Aquileia (unpublished data). characterised by a seriate porphyritic texture (PI 25e30 vol.…”
Section: Etnean Hawaiites and Mugearites From Mongibello (And Basaltsmentioning
confidence: 99%
“…Fortunately, seeing that volcanic complexes occur in few regions of the Mediterranean basin, volcanic rocks exploited for millstones may be very important markers for reconstruction of ancient commercial and communication routes. Old and recent works (Peacock, 1980(Peacock, , 1986(Peacock, , 1989Ferla et al, 1984;WilliamsThorpe, 1988;Williams-Thorpe and Thorpe, 1989, 1990, 1993Lorenzoni et al, 1996Lorenzoni et al, , 2000aOliva et al, 1999;Antonelli et al, 2000Antonelli et al, , 2001Antonelli et al, , 2004Antonelli et al, , 2005Renzulli et al, 2002a;Santi et al, 2004;Buffone et al, 2003) have combined to establish a useful petrographic, geochemical and historical database on the source areas for the grinding tools used in Mediterranean countries from the Neolithic to the Roman periods.…”
Section: Introductionmentioning
confidence: 96%
“…These few data is used in the following to check if a Pannonian provenance can be considered. Antonelli et al (2004) considered a possible provenance of grinding tools found in Istria (Croatia) and the Karst region (Italy/ Slovenia) from Mt. Etna, so, as an export of stone tools to this region can be taken into account, the millstones are additionally compared to lavas from Etna, Pantelleria and Ustica.…”
Section: Pannonian Basin: Millstones From Lower Austriamentioning
confidence: 99%